Effectiveness of Mindfulness-Based Relapse Prevention Group Therapy and Treatment as Usual on Positive and Negative Perfectionism in Men with Opioid Use Disorder: A Comparative Investigation - Rezvaneh Asadi Asadabad; Saeed Imani; Jalil Fathabadi; Alireza Noroozi (پژوهش‌های کاربردی روانشناختی, 2022)
The purpose of this study was to compare mindfulness-based relapse prevention (MBRP) group therapy and treatment as usual (TAU) in terms of their effectiveness on positive and negative perfectionism in men with opioid use disorder (OUD). The method of this study, due to its purpose, is an applied research and its method, in terms of the way of data collection, is an experiment with a pre-test-post-test. The population included men with opioid use disorder who were referred to Iranian National Center for Addiction Studies in Tehran in 2018. 36 patients were selected as the sample and randomly assigned to two groups: one group received a combination of MBRP group therapy and TAU and the other was treated with TAU only. Participants completed the Positive and Negative Perfectionism Scale (PANPS) at pretest, posttest, and follow-up. Data were statistically analyzed using a mixed-design ANOVA model. SPSS software (version 22) was used for data analysis. The results showed that none of the intergroup, intragroup, and interactive sources of variation in positive perfectionism were statistically significant. For negative perfectionism, the differences between the study phase groups were significant. The Bonferroni method was applied to examine the difference scores in the test phases and showed that the mean score decreased significantly in the posttest and follow-up phases compared with the pretest. According to these results, MBRP was effective in reducing negative perfectionism, but we cannot find any differences in the effectiveness of the therapies. These results indicate that MBRP can be considered an effective therapeutic approach for reducing negative perfectionism in individuals with OUD.